Effects of relaxin in a co-culture of Sertoli and germ cells - Porto, Catarina S.; Porto, Catarina S.; Lazari, Maria F.M. (Italian Journal of Anatomy and Embryology, 2014)
Spermatogenesis is controlled by FSH, testosterone and paracrine factors produced by Sertoli cells. The knockout of relaxin decreases sperm maturation in mice. Studies from our laboratory have shown that relaxin and its receptor RXFP1 are expressed in rat Sertoli cells, and exogenous relaxin stimulates Sertoli cell proliferation. Relaxin receptors are also detected in the rat germ cells at specific stages of development. Relaxin could therefore affect spermatogenesis either indirectly, by stimulating Sertoli cell proliferation, or directly, by affecting germ cells. The aim of the present study was to explore a role of relaxin at specific stages of spermatogenesis using a co-culture of rat Sertoli and germ cells. Relaxin seems to increase the number of pre-meiotic and meiotic cells.